If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5m+9)+2=36
We simplify the equation to the form, which is simple to understand
(5m+9)+2=36
Remove unnecessary parentheses
5m+9+2=36
We move all terms containing m to the left and all other terms to the right.
+5m=+36-9-2
We simplify left and right side of the equation.
+5m=+25
We divide both sides of the equation by 5 to get m.
m=5
| 5x^3-18-60= | | m(m+8n)+7n(m+8n)=0 | | 2h-5=5 | | 9a+42=12 | | 2y-8=-8 | | r/2+6=-3 | | A+42=12 | | 39=x+3x-1 | | (7+x)=2 | | ax+y= | | 7y=2x+25 | | (3p-3)=3 | | 12x-12=-2 | | 6g-4h=kforg | | 45=-4x+x+9 | | 3x+8+6x+7=7x+15 | | 4+6(2s+2)= | | (-3r)4(r+2)=11 | | (5+a)=14 | | X+2x+3x-7=-2.5 | | 46.50+15=5.25x | | 4/18y+28=0 | | 8-(-b-2)=11 | | 2a+6+7a=8 | | 7x-8+2(2x+1)=-5(x+2) | | 5x+8=6x+56 | | -(t+5)-4=-2(t-6) | | 2(x+1)+3=17 | | 3+-5+-2= | | 8+6x+7x=125 | | 2(a+5)=54 | | -9/-1 |